2004
DOI: 10.1002/jcb.20361
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol stimulates lipolysis in lipid‐laden RAW 264.7 macrophages

Abstract: This study investigated the effect of magnolol, a compound isolated from Magnolia officinalis, on lipolysis in lipid-laden RAW 264.7 macrophages. Treatment of macrophages with magnolol led to dissolution of lipid droplets. This phenomenon was accompanied by a dose-dependent release of glycerol and cholesterol and a concomitant reduction in intracellular levels of glycerol and cholesterol. Furthermore, adipose differentiation-related protein (ADRP), a lipid droplet-associated protein, was down-regulated by magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
0
23
0
2
Order By: Relevance
“…In a series of magnolol‐related studies, we found that magnolol also induces lipolysis in lipid‐laden RAW264.7 macrophages [13] and sterol ester‐loaded 3T3‐L1 preadipocytes, and the signaling pathway of the latter event involves ERK [14]. However, whether the same signaling pathway accounts for magnolol‐induced steroidogenesis in adrenal cells has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of magnolol‐related studies, we found that magnolol also induces lipolysis in lipid‐laden RAW264.7 macrophages [13] and sterol ester‐loaded 3T3‐L1 preadipocytes, and the signaling pathway of the latter event involves ERK [14]. However, whether the same signaling pathway accounts for magnolol‐induced steroidogenesis in adrenal cells has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[1] This transformation is exploited for the construction of complex carbon architectures. [5,6] In particular, nonsymmetric 2,2'-biphenols have exceptional properties as building blocks for ligands in molecular catalysis, [7] bioactive materials, [3] and natural products. [5,6] In particular, nonsymmetric 2,2'-biphenols have exceptional properties as building blocks for ligands in molecular catalysis, [7] bioactive materials, [3] and natural products.…”
mentioning
confidence: 99%
“…Since magnolol stimulated steroidogenesis in rat adrenal cells (Wang et al, 2000) and lipolysis in lipid-laden macrophages (Chen et al, 2005) through a pathway independent of the cAMP-PKA system, all these results indicate that lipolysis in adipocytes and lipid-laden macrophages is mediated via different signal transduction pathways. Further studies are required to investigate the underlying mechanism through which magnolol regulates lipid metabolism in macrophages.…”
Section: Effect Of No On Lipolysis In Lipid-laden Macrophages (A)mentioning
confidence: 85%